AIAA Guidance, Navigation, and Control Conference 2010
DOI: 10.2514/6.2010-8293
|View full text |Cite
|
Sign up to set email alerts
|

A Human-in-the Loop Exploration of the Dynamic Airspace Configuration Concept

Abstract: An exploratory human-in-the-loop study was conducted to better understand the impact of Dynamic Airspace Configuration (DAC) on air traffic controllers. To do so, a range of three progressively more aggressive algorithmic approaches to sectorizations were chosen. Sectorizations from these algorithms were used to test and quantify the range of impact on the controller and traffic. Results show that traffic count was more equitably distributed between the four test sectors and duration of counts over MAP were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In contrast to the prior papers on our 2009 study [8][9][10] , this paper focuses on the implications of the results in terms of feasible sector design and boundary change considerations for the FAM. Over-the-shoulder observations of the operations and feedback from the subject matter experts (SMEs) on the "goodness" of the airspace design have suggested that other cognitively-driven factors, such as the spatial relationship between upstream/downstream sectors, may also play a role when there is a high degree of airspace complexity associated with the reconfiguration.…”
Section: Other Sector Design and Boundary Change Considerationsmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast to the prior papers on our 2009 study [8][9][10] , this paper focuses on the implications of the results in terms of feasible sector design and boundary change considerations for the FAM. Over-the-shoulder observations of the operations and feedback from the subject matter experts (SMEs) on the "goodness" of the airspace design have suggested that other cognitively-driven factors, such as the spatial relationship between upstream/downstream sectors, may also play a role when there is a high degree of airspace complexity associated with the reconfiguration.…”
Section: Other Sector Design and Boundary Change Considerationsmentioning
confidence: 91%
“…A human-in-the-loop (HITL) simulation was conducted in the Airspace Operations Laboratory at the NASA Ames Research Center in 2009 to address some of the questions posed above 8,9 . Traffic scenarios with varying types and severity of boundary changes (BCs) were used to test their impact on the controllers.…”
Section: Exploring the Feasibility Of Flexible Airspace Reconfigumentioning
confidence: 99%
“…A human-in-the-loop simulation was conducted in 2010 [2,3] in the Airspace Operations Laboratory at NASA Ames Research Center to test the FAM concept, as a follow up to a previous study [4]. It comprised participants choosing airspace configuration from a set of algorithm-generated ones that best solved traffic imbalance problems due to weather deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Homola et al [32] showed how new on-demand reconfigurations could be implemented to balance sector traffic load and minimize over-capacity time periods without compromising safety, but at the cost of increasing controller task-load and workload ratings. Lee et al [15] and Jung et al [31] identified percent airspace volume and number of aircraft transferred as the primary contributors to reconfiguration workload for the same study.…”
Section: Reconfiguration Complexity Metricsmentioning
confidence: 99%